Rapamycin treatment dose‐dependently improves the cystic kidney in a new ADPKD mouse model via the mTORC1 and cell‐cycle‐associated CDK1/cyclin axis. Issue 8 (28th February 2017) - Li, Ao; Fan, Song; Xu, Yuchen; Meng, Jialin; Shen, Xufeng; Mao, Jun; Zhang, Li; Zhang, Xiansheng; Moeckel, Gilbert; Wu, Dianqing; Wu, Guanqing; Liang, Chaozhao
Abstract: Although translational research into autosomal dominant polycystic kidney disease (ADPKD) and its pathogenesis has made considerable progress, there is presently lack of standardized animal model for preclinical trials. In this study, we developed an orthologous mouse model of human ADPKD by cross‐mating Pkd2 conditional‐knockout mice ( Pkd2 f3 ) to Cre transgenic mice in which Cre is driven by a spectrum of kidney‐related promoters. By systematically characterizing the mouse model, we found that Pkd2 f3/f3 mice with a Cre transgene driven by the mouse villin‐ 1 promoter ( Vil ‐Cre; Pkd2 f3/f3 ) develop overt cysts in the kidney, liver and pancreas and die of end‐stage renal disease (ESRD) at 4–6 months of age. To determine whether these Vil ‐Cre; Pkd2 f3/f3 mice were suitable for preclinical trials, we treated the mice with the high‐dose mammalian target of rapamycin (mTOR) inhibitor rapamycin. High‐dose rapamycin significantly increased the lifespan, lowered the cystic index and kidney/body weight ratio and improved renal function in Vil ‐Cre; Pkd2 f3/f3 mice in a time‐ and dose‐dependent manner. In addition, we further found that rapamycin arrested aberrant epithelial‐cell proliferation in the ADPKD kidney by down‐regulating the cell‐cycle‐associated cyclin‐dependent kinase 1 (CDK1) and cyclins, namely cyclin A, cyclin B, cyclin D1 and cyclin E, demonstrating a direct link between mTOR signalling changes and the polycystin‐2 dysfunction in cystogenesis. Our newly developed ADPKD model provides a practical platform for translating in vivo preclinical results into ADPKD therapies. The newly defined molecular mechanism by which rapamycin suppresses proliferation via inhibiting abnormally elevated CDK1 and cyclins offers clues to new molecular targets for ADPKD treatment.